The effects of rice bran oil on left ventricular systolic function, cardiometabolic risk factors and inflammatory mediators in men with coronary artery disease: a randomized clinical trial. Issue 10 (21st April 2021) - Mahdavi-Roshan, Marjan; Salari, Arsalan; Ghorbani, Zeinab; Nikpey, Zahra; Haghighatkhah, Motahare; Fakhr mousavi, Aboozar; Gholipour, Mahboobeh; Pourfarzad, Amir
Abstract : In present study, we explored the effects of rice bran oil (RBO) in adjunct to conventional medical therapy on left ventricular ejection fraction (LVEF), cardiometabolic risk factors, and inflammation in males with coronary artery disease (CAD). Abstract : Background / objective : In the current study, we aimed to explore the effects of rice bran oil (RBO) in adjunct to conventional medical therapy on left ventricular ejection fraction (LVEF), cardiometabolic risk factors, and inflammatory mediators in male patients with coronary artery disease (CAD). Subjects / methods : The present randomized controlled trial included 40 men diagnosed with CAD (mean age = 55.76 years) who were randomly allocated into two groups to receive either 30 grams per day of RBO (intervention group) or sunflower oil (control group) plus a standard diet for eight weeks. At the initial visit, demographic and anthropometric data and blood samples were collected. LVEF levels and serum concentrations of lipid profile, glucose, uric acid, hs-CRP, and TNF-α were investigated. Results : A total of 37 participants completed the study ( n = 18 in the intervention group, n = 19 in the control group). Analysis of covariance (ANCOVA) adjusted for baseline values, age and body mass index revealed that RBO significantly improved LVEF (51.34%) and reduced triglyceride (125.01 mg dl −1 ), blood sugar (110.4 mg dl −1 ), total cholesterol (123.01 mg dl −1 ) and low density lipoprotein (56.88 mg dl −1 ) levels compared to sunflower oil ((45.56%), (155.93 mg dl −1 ), (128.94 mg dl −1 ), (163.93 mg dl −1 ) and (83.79 mg dl −1 ), respectively) following a 8-week trial ( P -values < 0.05). Additionally, the test demonstrated that RBO consuming patients had significantly lower levels of serum uric acid (4.60 mg dl −1 ), TNF-α (6.99 ng L −1 ) and hs-CRP (2.11 mg L −1 ) compared to the control group ((5.92 mg dl −1 ), (15.23 ng L −1 ), (4.47 mg L −1 ), respectively) ( P -value < 0.05). However, no significant changes were found regarding weight, blood pressure or serum HDL levels throughout the trial. Conclusion : Consumption of 30 grams per day RBO within a standard diet could be considered an effective non-pharmacological approach in improving LVEF, cardiometabolic risk factors, and inflammatory state in CAD. However, future trials are recommended for more clarification.